PENGARUH SENAM GERAK LATIHAN OTAK DENGAN FUNGSI KOGNITIF LANSIA DI PANTI WERDA INAKAKA AMBON PROVINSI MALUKU - Bazrul Makatita; Remsy Waimese (Pasapua Health Journal, 2021)
Introduction: Based on the results of preliminary data collection obtained at the Inakaka Ambon Nursing Home, Maluku province, the total number of elderly people living is 157 people, in 2018 there were 54 people, 35 women and 19 men, in 2019 there were 50 people, 27 women and 23 men, and in 2020 there are 53 people, 30 women and 23 men with a total of 260 people. Objective: The aim of the research was to find out that brain exercises are exercise for the elderly at the Inakaka Ambon Nursing Home, Maluku Province. Method: The research design used in this study is correlational in nature, namely by compiling a cross-sectional approach to research design or studying the influence of two or more variables on a situation or sample group Results: The results of data that have been collected, processed and analyzed using a computer and statistical program (SPSS) VERSION 23. Univariate data analysis and bivariate analysis with pre-test post-test (p <0.05). Bivariate results showed that there was an effect of brain exercise on cognitive function in the elderly (p=0.026). Conclusion: The conclusion in this study shows that there is an influence between brain exercises and cognitive function of the elderly at the Inakaka Ambon Nursing Home, Maluku Province.